Q: What is factorization of this trinomial -4x plus 11x - 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

If you mean: 6x-4x-2+11x then it can be simplified to 13x-2

(4x^4 - x³ + 17x² + 11x + 4) ÷ (4x + 3) = x³ - x² + 5x - 1 remainder 7. Do the division via long division, looking at the highest power of x in the dividend: _________________x³ ___- x²_ + 5x - 1 ________----------------------------------- 4x + 3 | 4x^4 - x³ + 17x² + 11x + 4 _________4x^4 + 3x³ _____________________ ← x³(4x + 3); x³ in the quotient _________-------------- _______________- 4x³ + 17x² ______________ ← subtract and bring down next term (+ 17x²) _______________ -4x³ __ -3x² ______________ ← -x²(4x + 3); - x² in the quotient _______________--------------- ______________________ 20x² + 11x ________ ← subtract and bring down the next term (+ 11x) ______________________ 20x² + 15x ________ ← 5x(4x + 3); + 5x in the quotient ______________________ -------------- ______________________________ -4x + 4 ____ ← subtract and bring down the next term (+ 4) ______________________________ -4x - 3 _____ ← -1(4x + 3); -1 in the quotient ______________________________ -------- ___________________________________ 7 ______ ← subtract; no more terms to bring down, this is remainder.

Depends on the sign of the term in x. (4x - 12)(x - 4) or (4x + 12)(x + 4)

11X - 23 = 7X + 5 subtract 7X from both sides 11X - 7X - 23 = 7X - 7X + 5 4X - 23 = 5 add 23 to both sides 4X - 23 + 23 = 5 + 23 4X = 28 divide both sides integers by 4 (4/4)X = 28/4 X = 7 --------------------check in original equation 11(7) - 23 = 7(7) + 5 77 - 23 = 49 + 5 54 = 54 checks

(2x + 5)(2x + 5)

Related questions

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

-4x2 + 11x - 6 factors to: (-4x + 3) (x - 2)

(4x + 5)(4x + 5)

4x + 8 + 7x + 12 = 11x + 20

yes.it is.

Yes, 6x2 - 4x + 25 is a trinomial. This is because there are three terms (thus the name trinomial), which are "connected" by operations of addition and subtraction: 6x2, 4x, and 25.If you mean to ask how to factor this particular trinomial, please specify so in your question.

23 + 15x - 4x = 1215x - 4x = 12 -2311x = -11x= -1

11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3

11x - 21 = 7x + 3 4x = 24x = 6

Yes

Dividend: 4x^4 -x^3 +17x^2 +11x +4 Divisor: 4x +3 Quotient: x^3 -x^2 +5x -1 Remainder: 7

yes